2018
DOI: 10.1007/s11307-018-1191-1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging VEGF Receptors and αvβ3 Integrins in a Mouse Hindlimb Ischemia Model of Peripheral Arterial Disease

Abstract: In a mouse hindlimb ischemia model of peripheral artery disease, [Tc]scV SPECT tracer-targeting VEGF receptors showed a more robust signal than [Tc]RGD tracer-targeting αβ. Immunofluorescent analysis suggests that uptake of [Tc]scV and [Tc]RGD in damaged tissue is due to non-overlapping cell populations and reflects different dynamic processes and that enhanced uptake of [Tc]scV may be due to the presence of VEGF receptors on additional cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The radiotracer we used to image angiogenesis, [ 99m Tc]DOTA-PEG-scVEGF, is based on an engineered single-chain (sc) recombinant version of VEGF121, site-specifically derivatized with PEGylated chelator DOTA for radiolabeling with 99m Tc (14,15). scV/Tc and its receptor-selective versions show nanomolar affinity to VEGFR-1 and VEGFR-2 is readily internalized upon binding to the VEGF receptors, and it reliably detects VEGF receptor expression in murine models of atherosclerosis and angiogenesis [16,27]. This is the first study to show feasibility of molecularly targeting angiogenesis in response to vascular occlusion in a diabetic large animal model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The radiotracer we used to image angiogenesis, [ 99m Tc]DOTA-PEG-scVEGF, is based on an engineered single-chain (sc) recombinant version of VEGF121, site-specifically derivatized with PEGylated chelator DOTA for radiolabeling with 99m Tc (14,15). scV/Tc and its receptor-selective versions show nanomolar affinity to VEGFR-1 and VEGFR-2 is readily internalized upon binding to the VEGF receptors, and it reliably detects VEGF receptor expression in murine models of atherosclerosis and angiogenesis [16,27]. This is the first study to show feasibility of molecularly targeting angiogenesis in response to vascular occlusion in a diabetic large animal model.…”
Section: Discussionmentioning
confidence: 99%
“…On day 7 after vascular occlusion, pigs were sedated, intubated, and anesthetized as described above. 99m Tclabeled scV was prepared as previously described [16]. A dose of 296.37 ± 82.88 MBq (8.01 ± 2.24 mCi) of scV/Tc was injected through the ear vein catheter.…”
Section: Angiogenesis Imaging and Muscle Biopsiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using SPECT imaging of [ 99m Tc]DOTA-PEG-scVEGF that targets the VEGF receptor, Tekabe et al found a stronger signal for evaluating angiogenesis compared to another [ 99m Tc] radiotracer targeting the α V β 3 integrin . in a mice model of limb ischemia using femoral artery ligation [ 140 ]. Interestingly, immunofluorescent analysis revealed the uptake of these radiotracers is non-overlapping, and could potentially be used to assess different cell types and processes [ 140 ].…”
Section: Molecular Imaging In Assessment Of the Microcirculation In Padmentioning
confidence: 99%